Thermal properties of metal-halide perovskites. Issue 41 (13th October 2020) - Haeger, Tobias; Heiderhoff, Ralf; Riedl, Thomas
Abstract : The thermal properties of metal-halide perovskites are reviewed with respect to experimental findings, theoretical insights, dimensionalities, and phase transitions. Abstract : Aside from photovoltaics, metal-halide perovskite semiconductors have also emerged as an attractive platform for LEDs and even lasers. For all of them, performance and operational stability are strongly influenced by thermally activated processes. As a result, studying the thermal properties of halide perovskites has become increasingly important. In addition to thermal conductivity measurements, thermal diffusivity and heat capacity studies are becoming more and more relevant for the dynamic operation of these devices. Here, we will review the current state of knowledge on the thermal properties of metal halide perovskites, including both experimental findings and theoretical insights. We will highlight the impact of the perovskite dimensionality (3D, 2D, 0D) on the thermal properties and how these properties change across the various phase transitions of these perovskites. Our review will also discuss thermal measurement methods, which can be favourably used to determine the thermal properties of both bulk and thin film samples. Advanced comprehensive tools and strategies for systematic thermal analyses and property optimizations are discussed.